Investigating Olfactory Bulb Volume Reduction as a Potential Biomarker for Some Neuropsychiatric Disorders: A Narrative Review - Hamed Hajishah; Seyyed Amirhossein Salehi; Mohammadjavad Amini (Journal of Clinical and Basic Research, 2021)
The Olfactory bulb is a crucial structure involved in olfaction that is located in the ventral anterior of the forebrain. Due to physiological and anatomical connection between olfactory and emotion processing networks, olfactory dysfunction is seen in some psychiatric disorders. Strong evidences suggest that olfactory bulb volume can mirror olfactory system function. Due to this correlation, there has been an interest to investigate the possible correlation between reduction of olfactory bulb volume and some neuropsychiatric disorders. Nowadays, mental disorders are mostly diagnosed according to behavioural symptoms. Gradual progression of mental disorders and delayed onset of behavioral symptoms have increased the importance of finding objective biomarkers. Such biomarkers can improve treatment outcome, accuracy of diagnosis, and prognosis. It is hypothesized that the reduction of olfactory bulb volume could be a biomarker for some disorders. In this article, we reviewed studies on the association of olfactory bulb volume with depression, Alzheimer’s disease, Parkinson’s disease, migraine, and multiple sclerosis.